Toxic effects and mechanism of 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47) on Lemna minor. (February 2018) - Qiu, Nianwei; Wang, Renjun; Sun, Yuan; Wang, Xiushun; Jiang, Dacheng; Meng, Yuting; Zhou, Feng
Abstract: To investigate the toxic effect and mechanism of 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47) in aquatic plants, in vivo and in vitro exposure to BDE-47 were conducted. After 14-d exposure to 5–20 μg/L BDE-47, the growth of Lemna minor plants was significantly suppressed, and the chlorophyll and soluble protein contents in fronds markedly decreased. Accordingly, the photosynthetic efficiency (Fv/Fm, PI) decreased. When the thylakoid membranes isolated from healthy fronds was exposed to 5–20 mg/L BDE-47 directly in vitro for 1 h, the photosynthetic efficiency also decreased significantly. In both the in vitro (5–20 μg/L) and in vivo (5–20 mg/L) experiments, BDE-47 led to an increased plasma membrane permeability. Hence, we concluded that BDE-47 had a direct toxicity to photosynthetic membranes and plasma membranes. However, direct effects on the activities of peroxidase (POD), malate dehydrogenase (MDH) and nitroreductase (NR) were not observed by adding 5–20 mg/L BDE-47 into crude enzyme extracts. The malondialdehyde (MDA) and superoxide anion radical (O2 − ) contents in the BDE-47 treated fronds were higher than those in the control fronds, suggesting that L . minor can not effectively relieve reactive oxygen species (ROS). The data above indicates that BDE-47 is toxic to L . minor through acting directly on biomembranes, which induces the production of ROS and thus causes remarkable oxidative damage to cells. Graphical abstract: Image 1 Highlights: BDE-47 at 5–20 μg/L had significant toxicity to L. minor. BDE-47 caused a direct injury to plasma membrane and thylakoid membrane of L. minor. BDE-47 had no effect on the enzyme activity of NR, POD, MDH in the cytoplasm. BDE-47 induced remarkable oxidative damage in frond cells of L. minor.